Word-Level Translation Techniques in Medical Terms From English into Indonesian - Yohanis Rongre (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The aim of this study was to describe the use of translation techniques and the impact of the use of translation techniques on the accuracy and acceptability of medical terms in book of the Foundation Module: the midwife in the community. The method used in this research was a mixed method design, combining quantitative and qualitative approaches as it to discuss the quantification of the frequency of translation techniques used by the translator to translate medical terms and the impact of translation techniques applied on the accuracy and acceptability of the medical term translations. The source of data in this study is a book entitled Foundation Module: the midwife in the community and its Indonesian translation and 6 informants as well as a rater to assess the quality of medical terms translation.  The results of this study showed that translation of medical terms of total 334 data dominated by naturalized borrowing 32.63%, calque 16.77% and description technique 8.38%. Meanwhile, quality assessment of the accuracy level of the translation showed a highly accurate 80.24% and assessment of acceptability 86.53%. Mostly the techniques used in translating medical terms give a positive influence for the accuracy and acceptability level of translation because the techniques used delivery the same information from the source language into the target language which is accepted linguistically.